Patient respiratory‐triggered quantitative T2 mapping in the pancreas. Issue 2 (13th January 2019) - Vietti Violi, Naïk; Hilbert, Tom; Bastiaansen, Jessica A.M.; Knebel, Jean‐Francois; Ledoux, Jean‐Baptiste; Stemmer, Alto; Meuli, Reto; Kober, Tobias; Schmidt, Sabine
Abstract : Background: Long acquisition times and motion sensitivity limit T2 mapping in the abdomen. Accelerated mapping at 3 T may allow for quantitative assessment of diffuse pancreatic disease in patients during free‐breathing. Purpose: To test the feasibility of respiratory‐triggered quantitative T2 analysis in the pancreas and correlate T2 ‐values with age, body mass index, pancreatic location, main pancreatic duct dilatation, and underlying pathology. Study Type: Retrospective single‐center pilot study. Population: Eighty‐eight adults. Field Strength/Sequence: Ten‐fold accelerated multiecho‐spin‐echo 3 T MRI sequence to quantify T2 at 3 T. Assessment: Two radiologists independently delineated three regions of interest inside the pancreatic head, body, and tail for each acquisition. Means and standard deviations for T2 values in these regions were determined. T2 ‐value variation with demographic data, intraparenchymal location, pancreatic duct dilation, and underlying pancreatic disease was assessed. Statistical Tests: Interreader reliability was determined by calculating the interclass coefficient (ICCs). T2 values were compared for different pancreatic locations by analysis of variance (ANOVA). Interpatient associations between T2 values and demographical, clinical, and radiological data were calculated (ANOVA). Results: The accelerated T2 mapping sequence was successfully performed in all participants (mean acquisition time, 2:48 ± 0:43 min). Low T2 value variability was observed across all patients (intersubject) (head: 60.2 ± 8.3 msec, body: 63.9 ± 11.5 msec, tail: 66.8 ± 16.4 msec). Interreader agreement was good (ICC, 0.82, 95% confidence interval: 0.77–0.86). T2 ‐values differed significantly depending on age ( P < 0.001), location ( P < 0.001), main pancreatic duct dilatation ( P < 0.001), and diffuse pancreatic disease ( P < 0.03). Data Conclusion: The feasibility of accelerated T2 mapping at 3 T in moving abdominal organs was demonstrated in the pancreas, since T2 values were stable and reproducible. In the pancreatic parenchyma, T2 ‐values were significantly dependent on demographic and clinical parameters. Level of Evidence : 4 Technical Efficacy : Stage 1 J. Magn. Reson. Imaging 2019;50:410–416.